Wire-Induced Stent Crumpling Remedied By BailOut Crush Stenting; A Case Report - SMS, Azarisman; MA, Rosli (IIUM Medical Journal Malaysia, 2011)
We report a-56-year old army pensioner who presented initially to a peripheral hospital with acute ST-elevation inferior myocardial infarction thrombolysed with streptokinase. He was subsequently referred to the National Heart Institute (Institut Jantung Negara, Malaysia) for coronary revascularization. Coronary angiogram revealed an ectatic right coronary artery with discrete lesions at the proximal and distal segments stented with bare metal stents (BMS). Post dilatation shots revealed a wire-induced, distal dissection at the posterior left ventricular artery remedied by balloon angioplasty but resulting in balloon-induced crumpling of the distal BMS. We discuss the importance of sequential, distal-to-proximal coronary intervention, stent crumpling and remedial strategies.